A collection of diverse theoretical, philosophical and sociological writings on various aspects of the sonata principle - Christopher Ballentine (College of Music, 2024)
The diverse works presented in these two volumes bear a sit;nificant relationship· to ca.ch other and to a common underlying theme, whi.ch may be said to be an attempt to enlarge our aYmreness of the nature and the possibilities of the Sonata Principle. All were expressly written for publication; one has already been published.